Determination of lactose in milk by high performance liquid chromatography-evaporative light scattering detector with RCM-monosaccharide Ca2+ column - ZHU Xiaopeng; FU Shangchen; HAO Guo; NIU Pengfei; LIU Yongfeng (Shipin yu jixie)
Objective: To achieve rapid detection of lactose content in milk, a new method for the determination of lactose in milk based on RCM-monosaccharide Ca2+ column and high-performance liquid chromatography has been established. Methods: Milk was precipitated with protein in a 0.2 g/mL trichloroacetic acid solution, and the resulting filtrate was diluted 100 times and filtered with a membrane before entering a high-performance liquid chromatography system. It was separated by an RCM-monosaccharide Ca2+ column and detected by an evaporative light scattering detector. Results: The results showed that lactose had a good correlation between peak area and concentration in the linear range （20~100 mg/L）, with an R2 of 0.999 8. When the lactose spiking levels were 15, 40, and 80 mg/g, the recovery range was between 90.96% and 98.23%, the detection limit was 3.6 μg/g, and the quantitative limit was 12 μg/g, the lactose concentration was determined within 6 minutes. 11 commercial milk samples were measured by this method, and the results were consistent with the national standard method. Conclusion: The precision, repeatability, and recovery rate of this method met relevant regulations, and the detection results were accurate and time-consuming. It is suitable for rapid detection of lactose content in milk.